Platelets-Derived miR-200a-3p Modulate the Expression of ET-1 and VEGFA in Endothelial Cells by Targeting MAPK14 - Yang, Jie; Xu, Hong; Chen, Kejie; Zheng, Danni; Liu, Shuang; Zhou, Xia; Lin, Yapeng; Cheng, Hang; Luo, Qin; Yang, Min; Yan, Xiaoyan; Hao, Junli (Frontiers in Physiology, 2022)
The interaction between platelets and vascular endothelial cells plays a pivotal role in the pathophysiology of acute ischemic stroke (AIS), especially in atherosclerosis formation. However, the underlying mechanism is not entirely clear. The aim of this study was to elucidate the role of platelets-derived miRNA in the development of atherosclerosis and AIS. We evaluated the miRNA expression profiles of serum microvesicles (MV) in five AIS patients and five healthy controls using RNA-seq, and then measured the levels of selected platelets derived miRNAs by qRT-PCR. miR-200a-3p expression in the serum MV and platelets had increased to 1.41 (p < 0.05) and 3.29 times (p < 0.001), respectively, in AIS patients compared with healthy controls, and was modified by severity of AIS. We transferred Cy5-miR-200a-3p into platelets, collected and identified platelets-derived MV (PMVs). Then, the gene expression of p38 MAPK/c-Jun pathway was analyzed using both miR-200a-3p gain- and loss-of-function experiments and PMVs coincubation with HUVEC. The results showed that activated platelets remotely modulated endothelins 1 (ET-1) and vascular endothelial growth factor A (VEGFA) levels in HUVEC through the release of miR-200a-3p-containing PMVs via targeting MAPK14. The results of ROC analyses showed that combination of platelet miR-200a-3p, serum ET-1 and VEGFA levels had an AUC of 0.817, a sensitivity of 70%, and a specificity of 89%. Our results presented new evidence that activated platelets could remotely modulate ET-1 and VEGFA expression in HUVEC via releasing miR-200a-3p-enriched PMVs, which provides a potential miRNA-based predictive biomarker and therapeutic strategy for atherosclerosis and AIS.